Complications of tunneled and non-tunneled peripherally inserted central catheter placement in chemotherapy-treated cancer patients: a meta-analysis - Hong, Jiana; Mao, Xiaodan (Frontiers in Surgery, 2024)
BackgroundTunneled peripherally inserted central catheters (PICC) have potential to reduce complications compared to non-tunneled PICC in previous studies. Which is better is debatable. Thus, the aim to compare the effect of tunneled and non-tunneled PICC for cancer patients undergoing chemotherapy.MethodsEmbase, PubMed, Cochrane Library database, and CNKI were searched from inception to March 15, 2024. Odds ratios (ORs) with 95% confidence intervals (95% CIs) was calculated to assess the complications of tunneled and non-tunneled PICC for cancer patients undergoing chemotherapy using random- or fixed-effects models.ResultsA total of 12 articles were retrieved. Meta-analysis showed that tunneled PICC significantly decreased the risk of wound oozing (OR: 0.29, 95% CI: 0.20–0.41), infection risk (OR: 0.41, 95% CI: 0.20–0.85), thrombosis risk (OR: 0.26, 95% CI: 0.15–0.44), phlebitis risk (OR: 0.23, 95% CI: 0.13–0.40), and catheter dislodgement risk (OR: 0.33, 95% CI: 0.22–0.50) compared to non-tunneled PICC.ConclusionsThe subcutaneous tunneling technology has advantages over normal technique in decreasing PICC-related complications for cancer patients undergoing chemotherapy.Systematic Review RegistrationPROSPERO (CRD42024522862).